2019
DOI: 10.1073/pnas.1914557116
|View full text |Cite
|
Sign up to set email alerts
|

An allosteric PGAM1 inhibitor effectively suppresses pancreatic ductal adenocarcinoma

Abstract: Glycolytic enzyme phosphoglycerate mutase 1 (PGAM1) plays a critical role in cancer metabolism by coordinating glycolysis and biosynthesis. A well-validated PGAM1 inhibitor, however, has not been reported for treating pancreatic ductal adenocarcinoma (PDAC), which is one of the deadliest malignancies worldwide. By uncovering the elevated PGAM1 expressions were statistically related to worse prognosis of PDAC in a cohort of 50 patients, we developed a series of allosteric PGAM1 inhibitors by structure-guided op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…Pancreatic cancer (PC) is a malignant tumour in the clinic; although the disease occurrence rate is quite low, it is still likely to become the second leading cause of cancer-related death worldwide due to the extremely low 5-year survival rate of less than 5% [1][2][3] . Basically, the high mortality of patients with PC is attributed to the complex pathogenesis, and latency leads to a severe lack of early diagnostic methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatic cancer (PC) is a malignant tumour in the clinic; although the disease occurrence rate is quite low, it is still likely to become the second leading cause of cancer-related death worldwide due to the extremely low 5-year survival rate of less than 5% [1][2][3] . Basically, the high mortality of patients with PC is attributed to the complex pathogenesis, and latency leads to a severe lack of early diagnostic methods.…”
Section: Introductionmentioning
confidence: 99%
“…Cancers are typical metabolic diseases whose development indeed incurs substantial metabolic alterations 1,10 . The Warburg effect is defined as the overexpression of aerobic glycolysis in cancer cells that can shunt glycolytic intermediates into multiple metabolic pathways that generate nucleotides, lipids, and amino acids 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Phosphoglycerate mutase (PGAM) displays relatively high expression and activities in many malignant cancers, including PDAC. Via proteomic techniques, PGAM-1 is statistically indicated to be associated with a relatively poor prognosis in PDAC [ 152 ]. After knockdown of PGAM-1 expression, decreased glycolytic flux and reduced cell invasion were observed by detecting 3-PG and 2-PG levels and performing invasion experiments, respectively, but the association with proliferation was independent [ 36 ].…”
Section: Glycometabolic Rearrangements In Pancreatic Cancermentioning
confidence: 99%
“…Therefore, targeting PTMs, such as dephosphorylation and deacetylation, at some sites in PGAM-1 could attenuate PGAM-1 enzymatic activity and tumorigenesis for PDAC treatment. Recently, a newly developed and promising compound, KH3, was found to act as an allosteric suppressor of PGAM-1, showing satisfactory drug effects to downregulate glycolysis and cell proliferation with limited cytotoxicity to PDAC cells [ 152 ].…”
Section: Glycometabolic Rearrangements In Pancreatic Cancermentioning
confidence: 99%
“…Huang et al 51 revealed that F22, K100, and R116 of PGAM1 residues were critical for the binding of inhibitors and that compound 9i, an anthraquinone inhibitor, significantly decreased lung cancer cell proliferation in different cell lines, which is a promising inhibitor for PGAM1. Moreover, in the recent research of Wen CL et al 55 an allosteric inhibitor of PGAMI named KH3 has been explored that dramatically inhibited the proliferation of PDAC cell lines by hampering the canonical cancer metabolic pathways. In summary, inhibitors targeting PGAM1 have been developed rapidly.…”
Section: Summary Of Pgam1 Inhibitors and Research Directions To Explomentioning
confidence: 99%